2012
DOI: 10.3113/fai.2012.0877
|View full text |Cite
|
Sign up to set email alerts
|

Role of Collateral Ligaments in Metatarsophalangeal Stability: A Cadaver Study

Abstract: Direct repairs of both structures improved the stability of the joint but not back to normal. IO tendon transfer is a possible adjunct to collateral ligament repairs, but in itself is not sufficient to restore stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 32 publications
2
13
0
1
Order By: Relevance
“…Our novel surgical procedure consists of CL reconstruction without PP repair. Recently, a cadaveric study demonstrated that repair of the CL improved joint stability [29]. The clinical and radiological outcomes in the present study support the conclusions of the cadaveric study.…”
Section: Discussionsupporting
confidence: 88%
“…Our novel surgical procedure consists of CL reconstruction without PP repair. Recently, a cadaveric study demonstrated that repair of the CL improved joint stability [29]. The clinical and radiological outcomes in the present study support the conclusions of the cadaveric study.…”
Section: Discussionsupporting
confidence: 88%
“…Большинство методов восстановления подошвенной связки плюснефалангового сустава проводятся с рассечением связочного коллатерального аппарата, что нарушает биомеханику движений и усиливает их нестабильность [30]. Нередко даже при коррекции деформации оси первой плюсневой кости сохраняются и прогрессируют симптомы метатарзалгии [31].…”
Section: способы восстановления подошвенной связки плюснефалангового unclassified
“…The plantar plate inserts firmly to the bases of the proximal phalanges ( Figure 2) and serves as an important distal attachment of the plantar fascia [6]. It is anchored to the distal metaphyseal region of the lesser metatarsals by the collateral ligaments and each plantar plate apparatus is coupled together by the deep transverse metatarsal ligament [7]. The plantar plate is in direct contact with the lesser metatarsal heads during gait and functions as the primary static stabilizer of the lesser MTPJs [8].…”
Section: Anatomymentioning
confidence: 99%